Analisis Need dan Demand Pelayanan Kesehatan pada Pra-Lansia dan Lansia Wilayah Sumbersari Kota Malang - Anggraeni, Yuanita Dwi; Rasyidin, Ahmad Dimas; Fitriani, Amelia Salsabila; Safarina, Aufilana Mafaza; An-Khofiyya, Nida; Betay, Oskar; Rahmawati, Indana Tri (Universitas Negeri Malang, 2024)
Pre-elderly and elderly are age groups vulnerable to health issues thus requiring adequate healthcare facilities. Analysis of healthcare service need and demand is used to gauge the current and future demand for healthcare services. This research aims to analyze the needs and demands related to healthcare services among pre-elderly and elderly in the RW 2 and RW 3 areas of Sumbersari Subdistrict, Malang City. The method employed in this research is quantitative descriptive observational with a cross-sectional study design. Samples were determined through purposive sampling and data were collected using questionnaires, then analyzed using descriptive statistics presented in tabular form. The analysis results from 50 research samples show that 96% of respondents choose to seek healthcare services when ill. Additionally, 92% of respondents require a doctor when seeking treatment. The demand analysis results indicate that healthcare treatment facilities show 90% availability to the community, 90% of the community receives services from doctors, and 92% find the services friendly and satisfactory. From this research, respondents exhibit high demand for healthcare services and the demand for healthcare service facilities has been well received by the community, with individuals expressing satisfaction with the healthcare services provided.